A Medieval Bright Star Table: The Non-Ptolemaic Star Table in the Īlkhānī Zīj. (August 2016) - Mozaffari, S. Mohammad
The Īlkhānī zīj compiled by Naṣīr al-Dīn al-Ṭūsī and his colleagues in the first period of the astronomical activities (the 1260s and early 1270s) in the Maragha observatory includes a star table collecting important observations of Islamic astronomers from the early ninth century through the third quarter of the thirteenth century, including the Mumtaḥan astronomers, Ibn al-A'lam, Ibn Yūnus, as well as the Maragha astronomers themselves. This table gives the ecliptical coordinates of 18 bright stars in comparison with Ptolemy's corresponding values. This medieval bright star table is especially interesting for two reasons: first, it provides reliable evidence for the examination of the accuracy of the observations made and the instruments employed (notably, an armillary sphere) in the Maragha observatory. Second, it facilitates a comparative study of the accuracy of stellar observations in medieval Middle Eastern astronomy in the period in question. We have obtained the result that the Maragha astronomers observed more accurate star longitudes than did their predecessors, while for the latitudes, all Islamic observers appear to have gained about the same degree of accuracy. We also discuss two delicate matters raised by this table: first, the problem of the use of the two different values for the rate of precession by the Maragha astronomers in order to convert earlier star longitudes to the epoch of the Īlkhānī zīj (1°/66 years for Ptolemy's longitudes and 1°/70 years for those measured by their Islamic predecessors); second, the change in the star latitudes essentially related to the various values measured by Ptolemy and the Islamic astronomers represented side-by-side in it. Finally, we briefly discuss a small celestial globe designed by the son of Mu'ayyad al-Dīn al-'Urḍī, the instrument-maker of the Maragha observatory.